Application of Risk Management to the Level of Financial Efficiency in BPD JAWA TENGAH - Tito Cayadi Luthfan; Gusganda Suria Manda; Suryanto Sosrowidigdo (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
Efficiency is one measure of bank performance. The efficiency of a bank is influenced by how management manages risk. This study measures the level of efficiency of conventional banking at PT Bank Pembangunan Daerah Jawa Tengah and the effect of financing risk, operational risk, and liquidity risk on the level of efficiency. Efficiency is measured by the Operational Expenditure method from Operating Income. The results of the calculation seen from the Operational Expenditure financial ratio report data from Operational Income show the level of efficiency of conventional banking at 80.65% in 2015-2019. The data used as the object of this study is the Bank Pembangunan Daerah Jawa Tengah for the period 2015-2019. Based on the results of statistical tests and discussion analysis, it is known that financing risk, operational risk, liquidity risk together have a simultaneous effect on the level of efficiency PT. Bank Pembangunan Daerah Jawa Tengah. From the results of hypothesis testing it was found that financing risk has a significant positive effect on the level of bank efficiency, operational risk does not have a significant negative effect on efficiency, and liquidity risk does not have a significant positive effect on the level of efficiency at PT Bank Pembangunan Daerah Jawa Tengah. And this is also reinforced by a significance value of 0.003 <0.05 (numbers are taken from ANOVA), which means that there is a statistically significant influence between financing risk, operational risk, liquidity risk on the level of efficiency